Aplikasi Pengundian dengan Pengunaan Cap Jari bagi Pemilihan Majlis Perwakilan Pelajar (MPP) Universiti Tun Hussein Onn, Pagoh - Atan, Muhammad Irfan; Mohd Azmi, Akif 'Izzuddin; Zakaria, Muhammad Syahiruddin Asyraf; Abdul Hamid, Mariam (Multidisciplinary Applied Research and Innovation, 2023)
This final year project is related to the design and development of the Fingerprint Voting System. This system is designed for courses for students of Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh campus. This system will be used by UTHM Pagoh students when voting for MPP and PPD candidates. The system is also designed because there are students who cheat in voting by using other students’ accounts to vote. By using this system, students need to scan their fingerprints before sending votes into the system. A total of 33 respondents were obtained to obtain feedback on this system. As a result of the study of this questionnaire, we found that this system can prevent students from cheating in voting.